The Effect of Automated Verbal Commands During Avalanche Transceiver Search on Acute Mental Stress and Arousal—A Mixed‐Methods Crossover Field Study - Wallner, Bernd; Caramazza, Fabio; Woyke, Simon; Winkler, Manuel; Regli, Ivo B.; Mair, Peter; Putzer, Gabriel; Strapazzon, Giacomo; Falk, Markus; Brugger, Hermann; Hüfner, Katharina (Brain and behavior, 2025)
ABSTRACT Background Companion rescue using avalanche transceivers can lead to a disproportionate increase in mental stress and arousal, which can negatively affect performance. The aim of this mixed‐methods field study was to assess the effects of automated verbal commands on mental stress and affective responses. Methods Participants performed two search trials using avalanche transceivers with either verbal commands (VOICE) or without verbal commands (NO VOICE) in simulated avalanche rescue scenarios. The study assessed perceived mental stress with a visual analogue scale (VAS 1–10 points) and used the Self‐Assessment‐Manikin with 9‐point Likert scales to measure affective response (valence, arousal, and dominance). Semistructured interviews were performed to assess the specific effects of verbal commands. Results Participants reported higher levels of mental stress after the trials than before the trials (−1.2 ± 2.3 points; p ≤ 0.001). A smaller increase (59.0 ± 8.2 s vs. larger increase [81.0 ± 11.5 s]) in mental stress, as detected in participants using VOICE navigation, resulted in shorter coarse search times. VOICE (Δ −1.2 ± 3.2 vs. Δ −0.6 ± 2.7 points; p = 0.041) showed a greater reduction in arousal, resulting in faster coarse search. In the qualitative interviews, the majority described VOICE navigation to be helpful. In the individual semistructured interviews, those subjects reporting a stress reduction through VOICE (38.5 ± 4.7 s vs. no stress reduction [107.4 ± 24.3 s]; p = 0.001) had a significantly faster coarse search time, and those who indicated VOICE to be helpful were faster in the coarse search (p = 0.013). Conclusions The study demonstrated that even a simulated avalanche rescue scenario results in increased mental stress levels. VOICE navigation may be an interesting option for companion avalanche rescue since it helps to reduce mental stress and arousal, thereby leading to shorter search times. The most significant limitation of the study was the setting of an experimentally created avalanche scenario, which cannot fully replicate all the environmental and psychological factors of a veritable burial situation. Avalanche search results in an increase in mental stress with longer coarse search times. VOICE navigation may be an interesting option for companion avalanche rescue since it helps to reduce mental stress and arousal, thereby leading to shorter search times.